Pelatihan dan Pendampingan Monitoring Ketuntasan Motorik Kasar Anak Usia Dini Pada Kelompok Guru Paud Banjarmasin Tengah - Fitrianto, Ari Tri; Habibie, Muhammad; Agus, Rahmadi (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
This service discusses the importance of children's gross motor skills in early childhood education. Teachers in Central Banjarmasin are actively involved in this service activity within the framework of the KKG. The approach taken through mentoring and training focused on providing an understanding to teachers related to the TGMD-2 test. The results of the community service show that many teachers do not fully understand the concept of children's gross motor completeness. Special training for PAUD teachers is also essential to use this test tool effectively. In addition, Parents also highlighted the role in supporting children's gross motor development. Collaboration between ECD teachers, parents, and academics in monitoring children's development will significantly impact their growth. Collaborative efforts of various parties are needed to create an environment that comprehensively supports children's gross motor development. With these steps, we hope children can grow and develop optimally in all aspects of their lives.